Antibiotikaresistens - djursjukskötarens roll i att förhindra spridningen - Klingén, Jenny (2014)
There are several different kinds of bacteria that has developed resistance against the antibiotic agents used in todays medicine. Most of them has evolved from the human health care but several of them has gone over to also cause problems in the animal health care. They often occur as nosocomial infections and the greatest risk of exposure to them is during health care. Since infections with a resistant bacterium can be difficult to treat, it is desirable to prevent this spread, especially since an animal treated in a hospital often is more susceptible to infection, due to their primary condition. In Sweden the current resistance situation is good and is yearly monitored by the Swedish Veterinary Antimicrobial Resistance Monitoring (SVARM) programme. To keep the prevalence of resistance down, a good compliance to hygiene in the animal hospitals and clinics in the country is necessary. The veterinary nurse has a lot of contact with the animals during their hospital stay, and is in a good position to make a cange in the work with hygiene. A different aspect is that most resistant bacteria is regarded as zoonoses, meaning that the personnel also have themselves to protect. Several studies from the human health care show a bad compliance, from the personnel, with the established hygiene protocolls which is a big problem since one weak link can make the whole hygiene chain collapse. More studies from the animal health care is indicated as well as interventions to try to increase the compliance.